Title: P2x7 Receptor Activation and Estrogen Status Drive Neuroinflammatory Mechanisms in a Rat Model for Dry Eye - David A. Bereiter; Mostafeezur Rahman; Fabeeha Ahmed; Randall Thompson; Nhungoc Luong; Julie K. Olson (Frontiers Media S.A., 2022)
Dry eye disease (DED) is recognized as a chronic inflammatory condition with an increase in tear osmolarity and loss of tear film integrity. DED is often accompanied by adverse ocular symptoms which are more prevalent in females than males. The basis for ocular hyperalgesia in DED remains uncertain; however, both peripheral and central neural mechanisms are implicated. A model for aqueous deficient DED, exorbital gland excision, was used to determine if activation of the purinergic receptor subtype 7, P2X7R, expressed by non-neural cells in peripheral and central trigeminal nerve pathways, contributed to persistent ocular hyperalgesia. Densitometry of trigeminal brainstem sections revealed increases in P2X7R, the myeloid cell marker Iba1, and the inflammasome, NLRP3, of estradiol-treated DED females compared to estradiol-treated sham females, while expression in DED males and DED females not given estradiol displayed minor changes. No evidence of immune cell infiltration into the trigeminal brainstem was seen in DED rats; however, markers for microglia activation (Iba1) were increased in all groups. Isolated microglia expressed increased levels of P2X7R and P2X4R, IL-1β (Ιnterleukin-1β), NLRP3, and iNOS (nitric oxide synthase). Further, estradiol-treated DED females displayed greater increases in P2X7R, IL-1β and NLRP3 expression compared to untreated DED females. Orbicularis oculi muscle activity (OOemg) evoked by ocular instillation of hypertonic saline (HS) was recorded as a surrogate measure of ocular hyperalgesia and was markedly enhanced in all DED groups compared to sham rats. Systemic minocycline reduced HS-evoked OOemg in all DED groups compared to sham rats. Local microinjection in the caudal trigeminal brainstem of an antagonist for P2X7R (A804598) greatly reduced HS-evoked OOemg activity in all DE groups, while responses in sham groups were not affected. Intra-trigeminal ganglion injection of siRNA for P2X7R significantly reduced HS-evoked OOemg activity in all DED groups, while evoked responses in sham animals were not affected. These results indicated that activation of P2X7R at central and peripheral sites in trigeminal pain pathways contributed to an increase in ocular hyperalgesia and microglia activation in DED males and females. Estrogen treatment in females further amplified ocular hyperalgesia and neuroimmune responses in this model for aqueous deficient DED.